Malignant chondroid syringoma: An unusual scalp tumor - Sundar, Geeta; Rao, Harish K (Indian Journal of Case Reports, 2022)
Chondroid syringomas are similar to mixed parotid tumors and present in both benign and malignant forms. Malignant chondroid syringoma (MCS) is a rare skin tumor that has a predilection for extremities, particularly in young women. It is even rarer to present as a scalp tumor with very few reported cases in the literature. We present a middle-aged woman, with a history of increasing fatigability of her right arm for the past 3 months who, on examination, was found to have scalp swelling and matted right posterior triangle lymph nodes. The working diagnosis on her was a large sebaceous cyst with secondary in the neck from an occult primary/non-Hodgkin’s lymphoma. Preliminary fine-needle aspiration was inconclusive. Imaging followed by wide excision of the tumor and the nearby occipital node was done. The final histopathological diagnosis was MCS with secondary in the lymph node. These tumors are aggressive and metastasize early. Radical surgery is the only hope of cure as adjuvant treatment is yet to be standardized.